Development of Character Education-Based Modules to Improve Student Learning Outcomes on Ecosystem Material - Dongoran, Pitri Hairani; Ulfa, Syarifah Widya (FKIP Universitas Lampung, 2023)
The research aims to develop educational, practical and effective character-based modules of valid, practical and effective ecosystem material. The study was conducted in SMAS Yayasan Reis Cendikia Tembung, Medan. In this study, research and development methods with model 4D. The results show assessments by experts at materials scored 92.31%, media experts at 96.43% and character education at 96.43% with valid and worthy criteria used in the learning process. Practical test results on the educators' response scores at 77.50% and learners at 78.63% which show modules are very practical to use. The module's application of learning results gained effective results with scoring a n-gain score of 0.73 with high criteria. Thus, the education-based core of ecosystem material is defined as valid, practical, and effective, and worthy of use in the learning process.Keywords: modules, ecosystems, development, character educationDOI: http://dx.doi.org/10.23960/jpmipa/v24i1.pp373-383